From Definition to Therapy: A Comprehensive Article Review of Galactosemia (World Journal of Experimental Biosciences, 2025)
Galactosemia is a medical disorder that affects the body’s ability to metabolize galactose. After infants ingest galactose from breast milk or formula, those with the condition can develop a life-threatening illness accompanied by feeding problems. Infants with galactosemia can be identified through newborn screening programs (NBS) or by symptoms that appear in the first weeks after birth. If untreated, infants may suffer kidney and liver damage, develop cataracts, and experience severe infections. Some countries offer newborn screening programs to help with the early detection and treatment of galactosemia. This article review aims to define galactosemia, its types, signs and symptoms, diagnosis, and ways it can be prevented or managed.